Answer:
(6y + 2)² = 4x²
Explanation:
Given: x - 1 = 3y
Dividing by 3,
⇒ y =
![$ (x - 1)/(3) $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yzqmmpicpj8vg75nfys6oy2gyfiy98jn6y.png)
Now, to determine 6y, multiply the equation throughout by 6y.
⇒ 6y =
![$ (6(x - 1))/(3) $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iq1syt04xgwssgxpfj62t4mpc1j732s0c3.png)
⇒ 6y = 2(x - 1)
⇒ 6y = 2x - 2
Now, for 6y + 2, add 2 on both sides.
⇒ 6y + 2 = 2x - 2 + 2
⇒ 6y + 2 = 2x
Finally, Squaring both sides, will give us (6y + 2)².
⇒ (6y + 2)² = (2x)²
= 4x² which is the required answer.